2012
DOI: 10.1128/jb.06762-11
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Genome of Bacillus amyloliquefaciens subsp. plantarum CAU B946 Contains a Gene Cluster for Nonribosomal Synthesis of Iturin A

Abstract: The genome of the rhizobacterium Bacillus amyloliquefaciens subsp. plantarum CAU B946 was 4.02 Mb in size and harbored 3,823 genes (coding sequences [CDS]). Nine giant gene clusters were dedicated to nonribosomal synthesis of antimicrobial compounds. Remarkably, strain CAU B946 possessed a gene cluster involved in synthesis of iturin A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 18 publications
(18 reference statements)
0
21
0
Order By: Relevance
“…It is likely that orthologs of the respective signature enzymes act in a different secondary metabolism pathway. The NPS ortholog in B. amyloliquefaciens for example, is part of the iturin A biosynthetic cluster [90] and the PKS in A. tereus seems to be part of a cluster with a second neighboring PKS gene. Mutations and genome reorganizations might be the driving force behind the re-shuffling and deletion of pathway genes and the creation of putatively novel metabolic products.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that orthologs of the respective signature enzymes act in a different secondary metabolism pathway. The NPS ortholog in B. amyloliquefaciens for example, is part of the iturin A biosynthetic cluster [90] and the PKS in A. tereus seems to be part of a cluster with a second neighboring PKS gene. Mutations and genome reorganizations might be the driving force behind the re-shuffling and deletion of pathway genes and the creation of putatively novel metabolic products.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, B. amyloliquefaciens FZB42 T isolated from the rhizosphere of Beta vulgaris (sugar beet) is widely used as a commercial plant growth-promoting rhizobacteria (PGPR), based on its abilities for plant root-colonizing and antibiotics production (Borriss et al, 2011; Chowdhury et al, 2015); while B. amyloliquefaciens LL3, isolated from fermented vegetables (Korean bibimbap), has been applied as an industrial strain for poly-Îł-glutamic acid production (Geng et al, 2011). Recently, whole-genome sequencing of numerous Bacillus strains has uncovered the molecular basis for their versatile performance under different environments (Kunst et al, 1997; Deng et al, 2011; Blom et al, 2012; He et al, 2012). Based on a comparative genomic analysis within Bacillus spp., Alcaraz et al indicated that the pathogen B. cereus possesses enriched genes involved in defense mechanisms, while the soil dweller B. subtilis harbors over-represented genes relevant to carbohydrates degradation (Alcaraz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…plantarum strains as biological control agents and plant growth promoters (Ongena & Jacques, 2008; PĂ©rez-GarcĂ­a et al ., 2011; Shan et al ., 2013; Sharma & Satyanarayana, 2013; Shi et al ., 2014). In recent years, interest in understanding the mode of action of these strains has led to many genomes being published for these strains (Blom et al ., 2012; Cai et al ., 2014; Dunlap et al ., 2013; Geng et al ., 2011; Hao et al ., 2012; Lefort et al ., 2014; Manzoor et al ., 2013; Nelson et al ., 2014; Niazi et al ., 2014a, b; Yang et al ., 2011; Zhang et al ., 2011, 2014). At the time of writing, 28 genome assemblies had been reported for B. amyloliquefaciens and two had been reported for B. methylotrophicus.…”
Section: Introductionmentioning
confidence: 99%